Genetic Deletion of Uncoupling Protein 3 Exaggerates Apoptotic Cell Death in the Ischemic Heart Leading to Heart Failure. Issue 3 (20th May 2013) - Perrino, Cinzia; Schiattarella, Gabriele G.; Sannino, Anna; Pironti, Gianluigi; Petretta, Maria Piera; Cannavo, Alessandro; Gargiulo, Giuseppe; Ilardi, Federica; Magliulo, Fabio; Franzone, Anna; Carotenuto, Giuseppe; Serino, Federica; et al.
Abstract : Background: Uncoupling protein 3 (ucp3) is a member of the mitochondrial anion carrier superfamily of proteins uncoupling mitochondrial respiration. In this study, we investigated the effects of ucp3 genetic deletion on mitochondrial function and cell survival under low oxygen conditions in vitro and in vivo. Methods and Results: To test the effects of ucp3 deletion in vitro, murine embryonic fibroblasts and adult cardiomyocytes were isolated from wild‐type (WT, n=67) and ucp3 knockout mice (ucp3 −/−, n=70). To test the effects of ucp3 genetic deletion in vivo, myocardial infarction (MI) was induced by permanent coronary artery ligation in WT and ucp3 −/− mice. Compared with WT, ucp3 −/− murine embryonic fibroblasts and cardiomyocytes exhibited mitochondrial dysfunction and increased mitochondrial reactive oxygen species generation and apoptotic cell death under hypoxic conditions in vitro (terminal deoxynucleotidyl transferase‐dUTP nick end labeling–positive nuclei: WT hypoxia, 70.3±1.2%; ucp3 −/− hypoxia, 85.3±0.9%; P <0.05). After MI, despite similar areas at risk in the 2 groups, ucp3 −/− hearts demonstrated a significantly larger infarct size compared with WT (infarct area/area at risk: WT, 48.2±3.7%; ucp3 −/−, 65.0±2.9%; P <0.05). Eight weeks after MI, cardiac function was significantly decreased in ucp3 −/− mice compared with WT (fractional shortening: WT MI, 42.7±3.1%; ucp3 −/− MI, 24.4±2.9; P <0.05), and this was associated with heightened apoptotic cell death (terminal deoxynucleotidyl transferase‐dUTP nick end labeling–positive nuclei: WT MI, 0.7±0.04%; ucp3 −/− MI, 1.1±0.09%, P <0.05). Conclusions: Our data indicate that ucp3 levels regulate reactive oxygen species levels and cell survival during hypoxia, modulating infarct size in the ischemic heart.